If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9p + -5q = 36 Solving 9p + -5q = 36 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5q' to each side of the equation. 9p + -5q + 5q = 36 + 5q Combine like terms: -5q + 5q = 0 9p + 0 = 36 + 5q 9p = 36 + 5q Divide each side by '9'. p = 4 + 0.5555555556q Simplifying p = 4 + 0.5555555556q
| [x^2-6x+5]=4 | | 8u^5/4u^2 | | (5x+6)(7x+10)-12x=13x | | d+27=-16 | | 1-1x/3=2x-1/3 | | 2x+34=4(5+x) | | 19=v+53 | | 2tg(x)*sec(x)-tg(x)=0 | | 2x-205x-205=0 | | 5000=x-(0.3*x) | | 2t(x)*sec(x)-tg(x)=0 | | 7x+4y^2= | | x+18=43 | | 8tag^2(x/2)=1secx | | 4x^-1/4x^-3 | | 4x^-1/4x-3 | | 2tan(x)sec(x)-tan(x)=0 | | 4148.9448=6.28r^2+(6.28)r(42.5) | | F^2+31f=0 | | x^2-(m-3)x+m=0 | | X^2+2x+1001=1 | | 2tan(x)*sec(x)-tan(x)=0 | | 7+6+n=-9+n+2n | | -5(x-2)=35 | | .0051x^3+.0043x^2+.104x+1.41= | | -8x+65=-x^2 | | f(x)=x^2+30x+225 | | a(2x+3)-b(3x+4)=10x+20 | | y=5(9z+80) | | 5y+(y+1)=35 | | -48x+8y+56=y | | f(x)*g(x)=(2x+1)(7x-6) |